"ᚁ is Beith and means birch” - an exploration of Ogham in online fanfiction featuring King Alfred the Great - Mussies, Martine (Studia Celtica Posnaniensia, 2024)
Through an analysis of three selected case studies, this study unveils how Ogham's integration into contemporary narratives generates fresh layers of meaning and revitalises this ancient alphabet. The chosen focus on Alfredian fanfiction offers a contextualised exploration of the role of this ancient Irish script in shaping novel interpretations, bridging historical languages with the digital age, and shedding light on how fan communities reconfigure cultural heritage across temporal and geographical boundaries within the dynamic landscape of internet culture. By employing a comprehensive approach, this research elucidates the intricate interplay between Ogham, historical narratives, and contemporary fan creativity, providing valuable insights into how this ancient script sparks innovative meanings and propels narratives within the digital realms of fan culture.